Genetic Characterization of Escherichia coli Populations from Host Sources of Fecal Pollution by Using DNA Fingerprinting - McLellan, Sandra L. (American Society for Microbiology, 2003)
Escherichia coli isolates were obtained from common host sources of fecal pollution and characterized by using repetitive extragenic palindromic (REP) PCR fingerprinting. The genetic relationship of strains within each host group was assessed as was the relationship of strains among different host groups. Multiple isolates from a single host animal (gull, human, or dog) were found to be identical; however, in some of the animals, additional strains occurred at a lower frequency. REP PCR fingerprint patterns of isolates from sewage (n = 180), gulls (n = 133), and dairy cattle (n = 121) were diverse; within a host group, pairwise comparison similarity indices ranged from 98% to as low as 15%. A composite dendrogram of E. coli fingerprint patterns did not cluster the isolates into distinct host groups but rather produced numerous subclusters (approximately >80% similarity scores calculated with the cosine coefficient) that were nearly exclusive for a host group. Approximately 65% of the isolates analyzed were arranged into host-specific groups. Comparable results were obtained by using enterobacterial repetitive intergenic consensus PCR and pulsed-field gel electrophoresis (PFGE), where PFGE gave a higher differentiation of closely related strains than both PCR techniques. These results demonstrate that environmental studies with genetic comparisons to detect sources of E. coli contamination will require extensive isolation of strains to encompass E. coli strain diversity found in host sources of contamination. These findings will assist in the development of approaches to determine sources of fecal pollution, an effort important for protecting water resources and public health.